A review of the genus Anteon Jurine, 1807 (Hymenoptera: Dryinidae) from South Korea, with description of a new species - Kim, Chang-Jun; Lee, Jong-Wook (Zootaxa, 2013)
Fifteen species of Anteon Jurine 1807 are recognized from South Korea, among which A. magnatum Kim & Lee, sp. nov. and ten newly recorded species: A. achterbergi Olmi, 1991; A. ephippiger (Dalman, 1818); A. esakii Yasumatsu, 1960; A. flavicorne (Dalman, 1818); A. insertum Olmi, 1991; A. medium Olmi, 1998; A. pilosum Xu, Olmi & He, 2010; A. reticulatum Kieffer, 1905; A. septentrionale Xu, He & Olmi, 2002; A. takenoi Olmi, 1995. A. esakii Yasumatsu and A. medium Olmi are also recorded from Russian Far East and China, Jilin, respectively (new records). Keys to South Korean species of Anteon are also provided.